Reflections on a novel coach education program: A narrative analysis - Hussain, A.; Trudel, P.; Patrick, T.; Rossi, A. (International Journal of Sports Science and Coaching, 2012)
This study examines the implementation of Triathlon Canada`s novel coach education program within the competition-development context from the perspective of the program designer; the High Performance Director (HPD). An interpretive approach was utilized to create a series of narratives to examine the background, perspectives and approaches used to construct the coach education program. Findings include the unique educational and practical background of the HPD and how it influenced him to design the coach education program the way he did. We also highlight a series of unique innovations for the Triathlon coaches entering the program including, a) submitting a portfolio of prior experiences, b) deemphasizing evaluation and certification and c) the HPD`s experiences of getting others to `buy` into the program. We also discuss the various instances of resistance encountered with implementing this type of program and contrast it with other types of conceptualizations of how coaches` learn.